A188 REAL-LIFE MANAGEMENT OF CHRONIC HEPATITIS C VIRUS INFECTION IN CANADA: DESCRIPTION OF PATIENT PROFILE, PROGNOSTIC FACTORS AND TREATMENT STRATEGIES. (1st March 2018) - Borgia, S; Elkhashab, M; Ghali, P; Kaita, K; Lee, S; Shafran, S; Tam, E; Trottier, B; Webster, D; Pinsonnault, C; Ackad, N
Abstract: Background: Most recent major treatment guidelines recommend considering the patient profile and baseline prognostic factors (genotype, fibrosis level, treatment history) in the management of chronic hepatitis C virus (HCV) infections (CHC). There is, therefore, a need to better characterize clinician decision-making in real-life CHC management in Canada. Aims: To describe the patient profile, prognostic factors and treatment strategies used in Canadian real-life CHC management. Methods: Multicenter chart review of CHC patients diagnosed from 2005 to 2012. Patient data were extracted for a minimum of 2 years after CHC diagnosis. Results: 250 patients were included with a mean (SD) follow-up after diagnosis of 5.9 (2.3) years. Table1 summarizes the patient/disease characteristics at CHC diagnosis and the mode of management. A majority of patients (70.4%) received some antiviral treatment, with a lower proportion of treated G1 patients vs. non-G1 patients (64% vs. 76.7%). The most common initial treatments were IFN/RBV dual therapy (68.4%) and NS3/4-containing IFN/RBV therapy (19.3%); Among non-G1 patients, 92.4% were treated with IFN/RBV dual therapy. SVR was achieved by 51.5% of patients (G1: 44.7%; non-G1: 62.2%), 19.3% relapsed and 11.1% were non-responders with initial treatment. The majority of treated patients (72.2%) experienced AEs, the most common ones being fatigue (33%), anemia (27.3%), insomnia (21.6%), neutropenia (18.8%). Two deaths were reported. Conclusions: Despite the majority of HCV patients having mild fibrosis and being treated, most frequently with dual IFN/RBV therapy, SVR rates were low prior to the all-oral DAA era, highlighting the need for more efficacious treatments and suggesting that recommendations to still use IFN are not justifiable. Funding Agencies: Abbvie corporation